Sulforaphane prevents angiotensin II‐induced cardiomyopathy by activation of Nrf2 through epigenetic modification. Issue 9 (1st April 2021) - Su, Xuling; Wang, Shudong; Zhang, Haiying; Yang, Ge; Bai, Yang; Liu, Pinyi; Meng, Lingbin; Jiang, Xin; Xin, Ying
Abstract: Nuclear factor erythroid 2‐related factor (Nrf2) is an important regulator of cellular antioxidant defence. We previously showed that SFN prevented Ang II‐induced cardiac damage via activation of Nrf2. However, the underlying mechanism of SFN's persistent cardiac protection remains unclear. This study aimed to explore the potential of SFN in activating cardiac Nrf2 through epigenetic mechanisms. Wild‐type mice were injected subcutaneously with Ang II, with or without SFN. Administration of chronic Ang II‐induced cardiac inflammatory factor expression, oxidative damage, fibrosis and cardiac remodelling and dysfunction, all of which were effectively improved by SFN treatment, coupled with an up‐regulation of Nrf2 and downstream genes. Bisulfite genome sequencing and chromatin immunoprecipitation (ChIP) were performed to detect the methylation level of the first 15 CpGs and histone H3 acetylation (Ac‐H3) status in the Nrf2 promoter region, respectively. The results showed that SFN reduced Ang II‐induced CpG hypermethylation and promoted Ac‐H3 accumulation in the Nrf2 promoter region, accompanied by the inhibition of global DNMT and HDAC activity, and a decreased protein expression of key DNMT and HDAC enzymes. Taken together, SFN exerts its cardioprotective effect through epigenetic modification of Nrf2, which may partially contribute to long‐term activation of cardiac Nrf2.